Peran Serta Perkembangan Hukum Perseroan di Indonesia dalam Maraknya ISU Penyimpangan Hukum Perseroan - Alfaatihah Intan Inayah; Nevarezita Rahmanda Arsyilhakim (Jurnal Hukum dan Sosial Politik, 2024)
Some of the existing issues examined in this study include: how is the development of a Limited Liability Company(hereinafter referred to as “PT”) in Indonesia after the enactment of Law Number 40 of 2007 on Limited Liability Company? This study uses normative research. How to obtain the data used in this study the use of secondary data collection techniques. The technique of collecting secondary data obtained from the study of literature. The analysis used in this study is qualitative analysis, the data obtained will be described in the form of information and explanations, will now be studied by experts, legal theories that are relevant, and the arguments of the own author. The results showed that PT was first set out in Article 36 through Article 56 Indonesian Commercial Code(Hereinafter referred to as “KUHD”). In addition, PT is regulated in Article 1233 to Article 1356 and Article 1618 to Article 1652 of the Indonesian Civil Code(Hereinafter referred to as “Kuhperdata”). New Orde, Indonesian Government issued Law Number 1 of 1995 on PT which became the lex specialis under Indonesian legal framework over KUHPerdata and KUHD. In the Era of Reform, Indonesian Government issued Law Number 40 of 2007 regarding on Indonesian Limited Liability Company Law. New things are regulated in the Law as follows: Social Responsibility and Environment (TJSL) which is an application of the concept of Corporate Social Responsibility (CSR), changes in the company's capital, the affirmation of the board of company’s responsibillity and registration of the company's own use of Information technololgy (IT) therefore that the company registration can be performed online.